PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN (Studi Empiris Pada Konsumen Wardah di Gerai Pusat Grosir Cililitan) (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
The purpose of this research is to find out the influence of product,brand image partial and simultaneous to the customer loyalty of product cosmetik Wardah. The data collected using the Rao pubra formula invloing 100 respondents which is Wardah cosmetik customers. Metodology this research is casual relation with test validity, reability tets, classic assumption test, correlation test, multipe linear regression test, t-test, F-test, and determinants. Base on result of reseach partial know that product quality (X1) influence on custemers loyality Wardah cosmetik, brand image (X2) not influence on custemer loyalty Wardah cosmetik. The qualty of product of the simultaneous effect on custumer loylity. The better the Product Quality, the Customer Loyalty will increase and the worse the Product Quality, the Customer Loyalty will decrease. The better the Brand Image the Customer Loyalty is increasing and the worse the Brand Image the customer loyalty will decrease.